GE_GERICHTE C/12563/2017 vom 23. Juli 2018 - GE Cour de justice (2018)
MESURE PROVISIONNELLE ; DIVORCE ; ATTRIBUTION DE L'EFFET SUSPENSIF ; LOGEMENT DE LA FAMILLE ; ORDRE D'ÉVACUATION | CPC.315.al4.letb